Cimbiosys: A platform for content-based partial replication - Wobber, Ted; Rodeheffer, Tom; Terry, Doug; Ramasubramanian, Rama; Marshall, Cathy (6th USENIX Symposium on Networked Systems Design and Implementation (NSDI '09), 2009)
Increasingly people manage and share information across a wide variety of computing devices from cell phones to Internet services. Selective replication of content is essential because devices, especially portable ones, have limited resources for storage and communication. Cimbiosys is a novel replication platform that permits each device to define its own content-based filtering criteria and to share updates directly with other devices. In the face of fluid network connectivity, redefinable content filters, and changing content, Cimbiosys ensures two properties not achieved by previous systems. First, every device eventually stores exactly those items whose latest version matches its filter. Second, every device represents its replication-specific metadata in a compact form, with state proportional to the number of devices rather than the number of items. Such compact representation results in low data synchronization overhead, which permits ad hoc replication between newly encountered devices and frequent replication between established partners, even over low bandwidth wireless networks.